The roles of wavelength in the gaseous toluene removal with OH from UV activated Fenton reagent. (July 2021) - Guo, Weiwei; Li, Tianqi; Chen, Qianru; Wan, Junfeng; Zhang, Jie; Wu, Bo; Wang, Yan
Abstract: The UV lights of different wavelengths were performed in boosting hydroxyl radicals (OH) generation from traditional Fenton reagent for the gaseous toluene removal. The Fenton, UV254 /Fenton and UV365 /Fenton processes were first adopted to eliminate gaseous toluene through the bubble column reactor, respectively. The stable toluene removal efficiency in 60 min was 85.31% in the UV365 /Fenton process, which was higher than other processes. The gaseous toluene was mainly oxidized into CO2 rather than other gaseous intermediates in the UV365 /Fenton process. For UV365 /Fenton process, the GC-MS tests were carried out to figure out the aqueous intermediates of gaseous toluene removal. The OH concentration in the UV365 /Fenton process was the highest among all the parallel tests via the EPR experiments and the quantificational measurements with coumarin as the probe. The iron ion in the aqueous solution was systematically evaluated with the experiments proceeding. The evolution of iron ion in the aqueous solution indicated that the fast reduction of Fe 3+ to Fe 2+ was assisted with 365 nm UV rather than 254 nm UV, which played a key point in the high gaseous toluene removal efficiency. This study demonstrated that the combination of UV365 irradiation and Fenton in the wet scrubbing reactor performed a synergistic effect on the gaseous toluene removal. Graphical abstract: Image 1 Highlights: The gaseous toluene removal efficiency was 85% in the UV365 /Fenton process. The removal route of gaseous toluene in the UV365 /Fenton process was speculated. The reduction of Fe 3+ was significantly enhanced by 365 nm UV irradiation.